A zinc coordination compound showing green photoluminescence - Zhu, Yu-Shu; Deng, Cui-Er; Zhang, Xue-Chun; Huang, Kun-Lin; Liu, Xi (Zeitschrift für Naturforschung. B, A journal of chemical sciences, 2023)
A novel three-dimensional coordination compound has been solvothermally synthesized based on a tetracarboxylate ligand H L (H L = 1,3,6,8-tetrakis(4-carboxylphenyl)pyrene), Zn L(H O) ·2DEF ( ) (DEF = ′-diethylformamide). Each Zn ion is coordinated by four carboxylate oxygen atoms from four L ligands and one oxygen atom from a water molecule to provide a distorted square-pyramidal geometry. Pairs of adjacent Zn cations are bridged by four carboxylate groups of four different L ligands to generate a paddle-wheel [Zn (COO) (H O) ] secondary building unit (SBU). Each SUB is further linked to four L ligands to give a three-dimensional framework with cds-type (CdSO -type) topology. The crystal structure has been determined via single-crystal X-ray diffraction, and the compound was characterized by elemental and thermal analysis, infrared spectroscopy, powder X-ray diffraction, and solid-state photoluminescence measurements.